Vloga besedilnega korpusa pri postavitvi geselskega članka v enojezičnem slovarju - Drstvenšek, Nina (Jezik in slovstvo, 2003)
The purpose of this paper is to demonstrate the use of a reference corpus in the compilation of an entry article in a monolingual dictionary. In the first part the contribution of corpora to the quality of lexicographical work is examined. Part two focuses on the cognitivr profile, the result of an analysis of corpus lines of a lexeme. Two types of linguistic data can be extracted from the cognitive profile: the sense of a lexeme, as manifested in the corpus, and the lexico-grammatical patterns associated with the senses. the paper explores how this type of linguistic information can inform the set-up of an entry article. Finally, in the third part predictions are made about the automation of the process.
Keywords: korpusno jezikoslovje; Corpus linguistics; leksikografija; lexicography; enojezični slovarji; Slovene; slovenščina